2015
DOI: 10.7439/ijbar.v6i1.1527
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal musculotendinous slip from Biceps Brachii to Pronator Teres: A Case Report

Abstract: Variations of upper limb muscles are quite commonly seen during dissection. Biceps Brachii take an edge on this, as it commonly has two or more than two sites of origin and insertion, where mode of insertion being both aponeurotic as well as tendinous. In present study, apart from common modes of insertion, an additional musculotendinous slip was seen running from the medial side of the muscle belly of Biceps Brachii to Pronator Teres and Flexor Carpi Radialis deep to the aponeurosis. The functional aspect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…8 Similarly, Trivedi et al described a case wherein additional muscle slips originated from the belly of the BB and were connected to the FCR and PT. 9 However, in the present case, only fleshy FCR muscle fibres originated from the lateral slip of the BA, without any accompanying PT fibres. Nayak et al reported a case of BA bifurcation into a larger medial slip and a small lateral slip.…”
Section: Discussionmentioning
confidence: 71%
“…8 Similarly, Trivedi et al described a case wherein additional muscle slips originated from the belly of the BB and were connected to the FCR and PT. 9 However, in the present case, only fleshy FCR muscle fibres originated from the lateral slip of the BA, without any accompanying PT fibres. Nayak et al reported a case of BA bifurcation into a larger medial slip and a small lateral slip.…”
Section: Discussionmentioning
confidence: 71%
“…Anatomical variations related to muscles of flexor compartment of forearm have been considered as subjects of many anatomical and radiological studies. It is not uncommon to get the variations related to FCR muscle [2][3][4][5][6][7][8]. Both congenital absence [2] and duplication in the form of two separate musculotendinous units, a FCR and a FCRB (flexor carpi radialis brevis) have been reported [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FCR muscle can receive additional slips from biceps tendon, brachialis, coronoid process or anterior oblique line of radius [6]. But very few reports regarding its origin from bicipital aponeurosis has been documented in medical literature [5,7,8]. Bhat et al in 2012 [5] observed variant tendinous slip arising from undersurface of aponeurotic extension of biceps brachii near its tendo aponeurotic bifurcation splitted into two bands, one continued with pronator teres and other joined with FCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 On every occasion when the bicipital aponeurosis is attached to pronator teres in the form of a musculotendinous extension; it ends up in a range of functional differences. 22 …”
Section: Deviations From the Normal Anatomymentioning
confidence: 99%